Implementation of AD8232 ECG Signal Classification Using Peak Detection Method For Determining RST Point - Martin Clinton Tosima Manullang; Jonathan Simanjuntak; Ahmad Luky Ramdani (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The medical world, especially those related to diseases and management of the heart uses ECG as a measurement tool. ECG has important points determined based on predetermined characteristics. The point is PQRST, where three of them are used as research objects in this paper. AD8232 is used as a research medium where the RST points must be determined in the AD8232 plot results by first determining the R points based on the highest peak. The results obtained were satisfactory wherein from 10 ECG graphic samples, 9 of them obtained RST point measurements which tended to be similar to conventional ECG measurements using millimeter paper as plotting media. Accuracy values reaching more than 90% indicate the reliability of the implementation results.